Journey Through the Movida: Feminism, Creativity and Otherness in Luisa Castro's El secreto de la lejía (2001) - Barbour, Catherine (Journal of Spanish Cultural Studies, 2026)
Painted as a celebration of creativity, plurality and feminist subcultures, la Movida madrileña was central to the 1980s nostalgia which permeated the Spanish narrative fiction produced at the beginning of the new millennium. Luisa Castro’s 2001 novel El secreto de la lejía recounts the lesser-represented experiences of a young Galician woman who moves to the Spanish capital to pursue a writing career during the Movida through an experimental, multigenre exploration of suffering and personal growth. This article shows how El secreto de la lejía unmasks dark realities of the Movida for the female outsider, contradicting interpretations of its universal social inclusivity. Through an intersectional feminist framework, it is argued that indicators of progress such as women’s independence, literary production and cultural plurality remain acutely subjected to discourses of power as the protagonist navigates the threatening atmosphere of elite artistic spaces at the cost of her own wellbeing. Castro’s novel fundamentally disrupts the mythologization of the Movida’s spirit of progress from a minoritized perspective, revealing the instability of the period and the enduring influence of heteropatriarchal power structures in Spain’s nascent democracy.
PUBLISHED
Keywords: Galician; Movida; Feminism; Luisa Castro; Spanish Narrative; Identities in Transformation; Inclusive Society; Manuscript, Book and Print Cultures; 20th and 21st Century Spanish Literature